Expert System Implementation Using Certainty Factor Method for Early Pregnancy Disease Detection - Nanda Syarla Hariyanti; Afina Lina Nurlaili; Firza Prima Aditiawan (bit-Tech, 2026)
Pregnancy requires continuous and accurate monitoring to prevent complications that may endanger both the mother and the fetus. Data from the 2024 Maternal Perinatal Death Notification (MPDN) system recorded an increase in maternal mortality, largely driven by delays in early diagnosis and late referral to appropriate healthcare facilities. These conditions highlight the need for decision-support technologies capable of providing timely and consistent early risk detection. This study develops HerBump, a web-based expert system designed to support the early identification of common pregnancy-related diseases by integrating the Certainty Factor (CF) method with expert medical knowledge. The novelty of this work lies in the use of CF to represent the degree of confidence from both experts and users, which helps improve diagnostic accuracy compared with conventional rule-based systems, especially in cases where symptoms are overlapping, incomplete, or vary between individuals. Evaluation results show that HerBump can generate early diagnostic outputs accurately and efficiently, supported by a System Usability Scale (SUS) score of 98.3 (Excellent) and Blackbox Testing that confirms all features function correctly across different scenarios. More broadly, the system has meaningful implications for maternal health, as it can support earlier interventions, enhance the consistency of risk assessments, and potentially help reduce maternal and infant mortality through faster and more reliable early detection. Its simple and scalable design also enables potential use in resource-limited areas, including regions with shortages of healthcare workers, with future development opportunities through expanded disease coverage and more diverse datasets to strengthen diagnostic reliability.